2007
DOI: 10.4161/cbt.6.9.4621
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hybrid 18F-FDG PET/CT and apoptosis induced by neoadjuvant chemotherapy in breast cancer

Abstract: Quantitative or semi-quantitative analysis of fluorine-18 fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) has been reported to correlate with the clinical and pathological response of tumors to preoperative treatment. This study was conceived to evaluate the correlation between hybrid 18 F-FDG PET/CT and apoptosis in breast cancer after neoadjuvant chemotherapy. Three cycles of neoadjuvant chemotherapy were given to forty-five patients with primary breast cancer proven by core needle biopsy. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…CT, PET, and PET/CT images of primary tumor showing good response to neoadjuvant chemotherapy from day 8 to after completion of chemotherapy. Most of these studies evaluated treatment response after one cycle of chemotherapy and demonstrated encouraging results [14][15][16][17][19][20][21][22][23][24][25][26][27][28]. However, a recent study by Rousseau et al using PET/CT, done in the largest population, demonstrated that the optimal timing to evaluate treatment response is after two cycles of NACT.…”
Section: Discussionmentioning
confidence: 96%
“…CT, PET, and PET/CT images of primary tumor showing good response to neoadjuvant chemotherapy from day 8 to after completion of chemotherapy. Most of these studies evaluated treatment response after one cycle of chemotherapy and demonstrated encouraging results [14][15][16][17][19][20][21][22][23][24][25][26][27][28]. However, a recent study by Rousseau et al using PET/CT, done in the largest population, demonstrated that the optimal timing to evaluate treatment response is after two cycles of NACT.…”
Section: Discussionmentioning
confidence: 96%
“…In a breast cancer clinical model, a decrease in 18 F-FDG uptake after neoadjuvant ChT was significantly and positively correlated with an increase in apoptotic index (i.e. a decrease of ≥20 % 18 F-FDG tumor-to-noise ratio from baseline was correlated with a mean increase in apoptotic index of 21±5 %) [61], and in a colorectal cancer clinical model, a [62]. In another clinical model of SCCHN, 18 F-FDG SUVmax and SUVmean with partial volume correction were correlated with the absolute number of apoptotic tumor cells (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…While apoptosis is an energy requiring process it appears that short term tumor response is directly correlated with a significant decrease in FDG uptake in both animal models and humans. 85,86 The relationship between apoptosis and glucose utilization at the early stage of cancer chemotherapy is complex and may depend on several factors including; the time of imaging after initiation of therapy and the mechanism(s) of drug action. Many chemotherapeutic agents damage DNA via free radical oxidation, alkylation and ionizing radiation inducing a massive activation of PARP-1 as mentioned previously.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%